Verbs in mothers’ input to six-month-olds: Synchrony between presentation, meaning, and actions Is related to later verb acquisition. - Nomikou, Iris; Koke, Monique; Rohlfing, Katharina (Brain Sciences)

“Can you teach me?” – Children teaching new words to a robot in a book reading scenario. - Grimminger, Angela; Rohlfing, Katharina (Proceedings of the 6th International Workshop on Child Computer Interaction (WOCCI 2017))

In Infants' Hands: Identification of Preverbal Infants at Risk for Primary Language Delay - Lüke, Carina; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf; Ritterfeld, Ute (CHILD DEVELOPMENT)
Early identification of primary language delay is crucial to implement effective prevention programs. Available screening instruments are based on parents' reports and have only insufficient predictive validity. This study employed observational measures of preverbal infants' gestural communication to test its predictive validity for identifying later language delays. Pointing behavior of fifty-nine 12-month-old infants was analyzed and related to their language skills 1 year later. Results confirm predictive validity of preverbal communication for language skills with the hand shape of pointing being superior compared to the underlying motives for pointing (imperative vs. declarative). Twelve-month-olds who pointed only with their open hand but never with their index finger were at risk for primary language delay at 2 years of age.

Reference as an Interactive Achievement: Sequential and Longitudinal Analyses of Labeling Interactions in Shared Book Reading and Free Play - Heller, Vivian; Rohlfing, Katharina (Frontiers in Psychology)

Benefits of repeated book readings in children with SLI - Rohlfing, Katharina; Ceurremans, Josefa; Horst, Jessica S. (Communication Disorders Quarterly)

Diagnostik des vorsprachlichen Kommunikationsverhaltens: Pilotstudie zur Konstruktvalidität eines neuen Elternfragebogens (Komm!-Bogen). - Müller, Christina; Grimminger, Angela; Caroli, Brigitte; Rohlfing, Katharina (Frühförderung Interdisziplinär)

Development of pointing gestures in children with typical and delayed language acquisition. - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Liszkowski, Ulf; Rohlfing, Katharina (Journal of Speech, Language, and Hearing Research)

An Interactive View on the Development of Deictic Pointing in Infancy. - Rohlfing, Katharina; Grimminger, Angela; Lüke, Carina (Frontiers in Psychology)

Preschoolers’ engagement in social interaction with an autonomous robotic system. - Lücking, Philipp; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (Proceedings of the IEEE ICDL-EpiRob 2016)

Vocal interactions at the dawn of communication: The emergence of mutuality and complementarity in mother-infant interaction. - Leonardi, Giuseppe; Nomikou, Iris; Rohlfing, Katharina; Rączaszek-Leonardi, Joanna (Proceedings of the IEEE ICDL-EpiRob 2016)

Pragmatic Frames for Teaching and Learning in Human–Robot Interaction: Review and Challenges - Vollmer, Anna-Lisa; Wrede, Britta; Rohlfing, Katharina; Oudeyer, Pierre-Yves (Frontiers in Neurorobotics)

Language meddles with infants‘ processing of observed actions - Sciutti, Alessandra; Lohan, Katrin Solveig; Gredebäck, Gustaf; Koch, Benjamin; Rohlfing, Katharina (Frontiers in Robotics and AI)

Language—at all times. Action and interaction as contexts for enriching representations. - Nomikou, Iris; Malte, Schilling; Heller, Vivien; Rohlfing, Katharina (Interaction Studies)

Embodied Language Learning and Cognitive Bootstrapping: Methods and Design Principles - Lyon, Caroline; Nehaniv, Chrystopher L.; Saunders, Joe; Belpaeme, Tony; Bisio, Ambra; Fischer, Kerstin; Forster, Frank; Lehmann, Hagen; Metta, Giorgio; Mohan, Vishwanathan; Morse, Anthony; Nolfi, Stefano; et al. (International Journal of Advanced Robotic Systems)
Co-development of action, conceptualization and social interaction mutually scaffold and support each other within a virtuous feedback cycle in the development of human language in children. Within this framework, the purpose of this article is to bring together diverse but complementary accounts of research methods that jointly contribute to our understanding of cognitive development and in particular, language acquisition in robots. Thus, we include research pertaining to developmental robotics, cognitive science, psychology, linguistics and neuroscience, as well as practical computer science and engineering. The different studies are not at this stage all connected into a cohesive whole; rather, they are presented to illuminate the need for multiple different approaches that complement each other in the pursuit of understanding cognitive development in robots. Extensive experiments involving the humanoid robot iCub are reported, while human learning relevant to developmental robotics has also contributed useful results. Disparate approaches are brought together via common underlying design principles. Without claiming to model human language acquisition directly, we are nonetheless inspired by analogous development in humans and consequently, our investigations include the parallel co-development of action, conceptualization and social interaction. Though these different approaches need to ultimately be integrated into a coherent, unified body of knowledge, progress is currently also being made by pursuing individual methods.
Keywords: Robot Language; Human Robot Interaction; HRI; Developmental Robotics; Cognitive Bootstrapping; Statistical Learning

Effekte von Objekt-Familiarisierung auf die frühe gestische Kommunikation. Individuelle Unterschiede in Hinblick auf den späteren Wortschatz - Grimminger, Angela; Lüke, Carina; Ritterfeld, Ute; Liszkowski, Ulf; Rohlfing, Katharina (Frühe Bildung)
There is ongoing discussion on the function of the early production of gestures with regard to whether they reduce children's cognitive demands and free their capacity to perform other tasks (e.g., Goldin-Meadow & Wagner, 2005) or whether young children point in order to share their interest or to elicit information from their caregivers (e.g., Begus & Southgate, 2012; Liszkowski, Carpenter, Henning, Striano & Tomasello, 2004). The different assumptions lead to diverse predictions regarding infants' gestural or multimodal behavior in recurring situations, in which some objects are familiar and others are unfamiliar. To examine these different predictions, we observed 14 children aged between 14 and 16 months biweekly in a semi-experimental situation with a caregiver and explored how children's verbal and gestural behaviors change as a function of their familiarization with objects. We split the children into two groups based on their reported vocabulary size at 21 months of age (larger vs. smaller vocabulary). We found that children with a larger vocabulary at 21 months had an increase in their pointing with words toward unfamiliar objects as well as in their total amount of words, whereas for children with smaller vocabularies we did not find differences in relation to their familiarization with objects. We discuss these findings in terms of a social-pragmatic use of pointing gestures.
Keywords: gesture; pointing; familiarity; individual differences

An Alternative to Mapping a Word onto a Concept in Language Acquisition: Pragmatic Frames - Rohlfing, Katharina; Wrede, Britta; Vollmer, Anna-Lisa; Oudeyer, Pierre-Yves (FRONTIERS IN PSYCHOLOGY)
The classic mapping metaphor posits that children learn a word by mapping it onto a concept of an object or event. However, we believe that a mapping metaphor cannot account for word learning, because even though children focus attention on objects, they do not necessarily remember the connection between the word and the referent unless it is framed pragmatically, that is, within a task. Our theoretical paper proposes an alternative mechanism for word learning. Our main premise is that word learning occurs as children accomplish a goal in cooperation with a partner. We follow Bruner's (1983) idea and further specify pragmatic frames as the learning units that drive language acquisition and cognitive development. These units consist of a sequence of actions and verbal behaviors that are co-constructed with a partner to achieve a joint goal. We elaborate on this alternative, offer some initial parametrizations of the concept, and embed it in current language learning approaches.
Keywords: language acquisition; pragmatics; infants' social learning; frames; learning and memory; developmental robotics

Preschoolers' engagement in social interaction with an autonomous robotic system - Lücking, Phillip; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (2016 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob))

Can 28-month-old children learn spatial prepositions robustly from pictures? Yes, when narrative input is provided. - Rohlfing, Katharina; Nachtigäller, Kerstin (Frontiers in Language Science)

How to learn the deictic shift through observation? - Krause, Franziska; Rohlfing, Katharina

Alignment to the Actions of a Robot - Vollmer, Anna-Lisa; Rohlfing, Katharina; Wrede, Britta; Cangelosi, Angelo (International Journal of Social Robotics)
Alignment is a phenomenon observed in human conversation: Dialog partners' behavior converges in many respects. Such alignment has been proposed to be automatic and the basis for communicating successfully. Recent research on human-computer dialog promotes a mediated communicative design account of alignment according to which the extent of alignment is influenced by interlocutors' beliefs about each other. Our work aims at adding to these findings in two ways. (a) Our work investigates alignment of manual actions, instead of lexical choice. (b) Participants interact with the iCub humanoid robot, instead of an artificial computer dialog system. Our results confirm that alignment also takes place in the domain of actions. We were not able to replicate the results of the original study in general in this setting, but in accordance with its findings, participants with a high questionnaire score for emotional stability and participants who are familiar with robots align their actions more to a robot they believe to be basic than to one they believe to be advanced. Regarding alignment over the course of an interaction, the extent of alignment seems to remain constant, when participants believe the robot to be advanced, but it increases over time, when participants believe the robot to be a basic version.
Keywords: learning; Human-robot interaction; Alignment; Robot social; Action understanding